Characterization of Weissella koreensis SK Isolated from Kimchi Fermented at Low Temperature (around 0 °C) Based on Complete Genome Sequence and Corresponding Phenotype - Mun, So Yeong (Microorganisms, 2020)
This study identified lactic acid bacteria (LAB) that play a major role in kimchi fermented at low temperature, and investigated the safety and functionality of the LAB via biologic and genomic analyses for its potential use as a starter culture or probiotic. Fifty LAB were isolated from 45 kimchi samples fermented at −1.5~0 °C for 2~3 months. Weissella koreensis strains were determined as the dominant LAB in all kimchi samples. One strain, W. koreensis SK, was selected and its phenotypic and genomic features characterized. The complete genome of W. koreensis SK contains one circular chromosome and plasmid. W. koreensis SK grew well under mesophilic and psychrophilic conditions. W. koreensis SK was found to ferment several carbohydrates and utilize an alternative carbon source, the amino acid arginine, to obtain energy. Supplementation with arginine improved cell growth and resulted in high production of ornithine. The arginine deiminase pathway of W. koreensis SK was encoded in a cluster of four genes (arcA-arcB-arcD-arcC). No virulence traits were identified in the genomic and phenotypic analyses. The results indicate that W. koreensis SK may be a promising starter culture for fermented vegetables or fruits at low temperature as well as a probiotic candidate.